Serum 25-hydroxyvitamin D is associated with stroke history in a reverse J-shape - Pan, Jue-heng; Wu, Shuo-long; Ma, Jing-xiang; Chang, Long; Zheng, Ying-feng; Wang, Xiao-dong (Frontiers in Neurology, 2023)
Background 25-hydroxyvitamin D [25(OH)D], the major form of vitamin D in the body, has a non-linear association with stroke risk. However, the association is not fully understood. The specific shape of the association and the ideal value of 25(OH)D related to minimum risk of stroke remain unclear. Aim We conducted the study to establish the correlation between circulating 25(OH)D and stroke history and determine the ideal value of 25(OH)D in relation to the lowest stroke prevalence. Methods Data from the National Health and Nutrition Examination Survey (NHANES) were used for analyzes. We used multivariate logistic regression analysis with fitted smooth curves to explore the relationship between 25(OH)D and self-reported stroke history. Subsequently, 40,632 participants were enrolled in the study. Results A reverse J-shaped association between 25(OH)D and stroke history was determined, where the lowest stroke prevalence for the 25(OH)D level was about 60 nmol/L. After adjusting for confounding factors, prevalence of stroke showed an increasing trend below and above the middle quintile (53.2–65.4 nmol/L) of 25(OH)D. Participants with 25(OH)D levels in the lowest quintile (≤ 39.3 nmol/L) had a 38% increased prevalence of stroke (OR 1.38, 95 %CI 1.12–1.70), while those in the higher level range of 25(OH)D (65.5–80.8 nmol/L) had a 27% higher stroke prevalence (OR 1.27, 95 %CI 1.03–1.57). Conclusion Using data from a large, cross-sectional cohort program, we found that circulating 25(OH)D was related to stroke history in a reverse J-shaped manner. Given how the causal relationship between circulating 25(OH)D and history of stroke has not been established, more high-quality evidence based on the reverse J-shaped feature is needed to elucidate the link between vitamin D and stroke risk, and the effect of vitamin D supplements on stroke prevention.